Utilization of Number Lines Through the Peer Teaching Method In Student Learning with Hearing Impairments - Edi Purwanta; Bayu Pamungkas; Diajeng Tyas Pinru Phytanza (Department of Special Education, 2020)
This research aims to describe the utilization of number line media through peer teaching methods in student learning with hearing impairments. This study used an action research design with research participants of class III SLB B Karnnamanohara Yogyakarta. The data collection techniques used in this study were participative observation, field notes, interviews, and documentation. Data analysis used data triangulation techniques. The results showed that (1) Teachers and students could be assisted in the learning process using number line media through the peer teaching method. (2) The peer teaching method combined with number line media helps to establish interactions between teachers and students in the learning process. (3) Student learning outcomes in Mathematics can achieve KKM scores after using number line media through the peer teaching method.